THE PRODUCTION AND PROPERTIES OF COCONUT STEM CHARCOAL IN THAILAND - J. Dootson; Peyanoot Naka; Maliwan Rattanapruk; Panit Ngangoranatigar (International Coconut Community, 1989)
A programme of experimentation and training on the production of charcoal from coconut stems in transportable metal k.ilns was carried out. Comparisons were made between different timber densities, preparation methods and kiln loading systems. Other timber sources and traditional kilns were used. The highest density coconut wood produced the best charcoal and extensive preparation was found to be necessary. Local clay kilns produced excellent charcoal, but were slow and needed considerable fuel. Coconut stem charcoal. production was markedly different from carbonisation of wood from dicotyledonous trees. The charcoal produced was found to have similar calorific value to that from other woods, but was faster‑burning and easier to ignite. Content of volatile matter was low and little ash was produced. The charcoal was often rather wet. A sample of consurners found that the charcoal was better than they had expected. The main complaint was the speed of burning.